A charged nanocomposite membrane via co-deposition of gallic acid and polyethyleneimine-silver for improving separation and antibacterial properties. (20th January 2023) - Zhu, Yihang; Huang, Zhonghua; Tang, Mengdi; Li, Qunxia; Liu, Yulong; Bai, Xinhui
Abstract: Pharmaceuticals have been continuously detected from surface water and groundwater. In order to improve the rejection performance of pharmaceuticals by a nanofiltration membrane (NF), a positively charged membrane was prepared by co-deposition of natural gallic acid and polyethyleneimine on the polyacrylonitrile hydrolysis membrane. Effects of gallic acid concentration, polyethylene imine concentration, reaction time, and the molecular weight of polyethylene imine were documented. The physical and chemical properties of the membrane were also investigated by surface morphology, hydrophilicity, surface charge, and molecular weight cut-off. The optimized membrane had a molecular weight cut-off of about 958 Da and possessed a pure water permeability of 74.21 L·m −2 ·h −1 ·MPa −1 . The results exhibited salt rejection in the following order: MgCl2 > CaCl2 > MgSO4 > Na2 CO3 > NaCl > Na2 SO4, while the rejection ability of pharmaceuticals is as follows: amlodipine > atenolol > carbamazepine > ibuprofen, suggesting that the positively charged membrane has enhanced retention to both divalent cations and charged pharmaceuticals. In addition, the antibacterial membrane was obtained by loading silver nanoparticles onto the positively charged membrane, which greatly improved the antibacterial ability of the membrane. HIGHLIGHTS: The NF membrane was prepared by using natural gallic acid that can be extracted from plants. Improved water permeation flux due to loose pore structure and excellent hydrophilicity of the modified NF membrane. Enhanced rejection ability of the membrane to both divalent cations and positively charged pharmaceuticals. Improved antibiological fouling performance by loading AgNPs on the modified NF membrane. Graphical Abstract